2019
DOI: 10.1039/c8ay02442a
|View full text |Cite
|
Sign up to set email alerts
|

Simplified analytical methodology for glucosinolate hydrolysis products: a miniaturized extraction technique and multivariate optimization

Abstract: Miniaturized extraction techniques are one of the most significant advances in analytical chemistry today.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…An exploratory analysis of the efficacy of different solvents to extract PEITC was performed; 1.00 g of the pulverized WC was suspended in 15 mL of 25 mM phosphate buffer pH 7.0 for 2 h at 37 • C to allow the hydrolysis of the glucosinolates [10]. Then, 0.15 g of surfactant (Genapol X-080, Tergitol 15-S-7), or 5 mL of n-hexane, or 5 mL of ACN/CF 10/7 mixture was added.…”
Section: Extraction Proceduresmentioning
confidence: 99%
See 3 more Smart Citations
“…An exploratory analysis of the efficacy of different solvents to extract PEITC was performed; 1.00 g of the pulverized WC was suspended in 15 mL of 25 mM phosphate buffer pH 7.0 for 2 h at 37 • C to allow the hydrolysis of the glucosinolates [10]. Then, 0.15 g of surfactant (Genapol X-080, Tergitol 15-S-7), or 5 mL of n-hexane, or 5 mL of ACN/CF 10/7 mixture was added.…”
Section: Extraction Proceduresmentioning
confidence: 99%
“…PEITC extracts were diluted and analysed by high-performance liquid chromatography (HPLC-DAD). The separation was carried out by applying the operating conditions described by Fusari, Ramirez, and Camargo [10], with slight modifications. Briefly, the operating conditions were as follows: gradient elution starts at 50% mobile phase A (ultra-pure water + 0.1% formic acid) and 50% mobile phase B (methanol + 0.1% formic acid), with a phase B increment up to 80% for 20 min, remaining isocratic for 10 min, and returning to 50% of phase B the next 5 min, at a continuous flow of 0.80 mL/min.…”
Section: Peit Chromatographic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Broccoli and cauliflower have higher content of I3C, I3A, and IAA, compared with Chinese cabbage and cabbage. This result is similar to previous work, where it was found that the indole content in reproductive tissues (flower and seed) were higher than in leaf tissue . The indole DIM was not detected (below the LOD of the method) in cauliflower and Chinese cabbage.…”
Section: Resultsmentioning
confidence: 99%